骨変形のない非復位性関節円板転位症例に対する顎関節腔洗浄療法・ 消炎鎮痛薬投与および開口練習併用療法における ステロイド薬注入の意義 - 栗田, 賢一; 鍋島, 弘充; 清水, 幹雄; 脇田, 壮; 中塚, 健介; 中島, 克仁; 小木, 信美; 服部, 雄紀; 矢島, 哲弥; 佐藤, 春樹 (日本口腔外科学会雑誌, 2010)
Purpose: Recent biochemical studies of synovial fluids indicate that temporomandibular joint (TMJ) symptoms are caused by intra-articular inflammation. There are various ways to manage such disorders.Arthrocentesis is one effective treatment for closed lock. The aim of this study was to evaluate the efficacy of arthrocentesis (steroid injection) followed by mouth opening exercises during non-steroidal anti-inflammatory drug (NSAID) theraphy as a primary treatment for closed lock. The ultimate goal was to increase the improvement rate and the number of patients with no TMJ dysfunction. Subjects and Methods: Subjects were selected from a series of patients with newly diagnosed closed lock who presented at Aichi-Gakuin University Hospital between January 2003 and December 2004. Sixty-two patients were confirmed to have closed lock with MRI. The patients underwent two consecutive sessions of arthrocentesis at a 2-week interval and were followed up every 2 weeks for 12 weeks. NSAID administration and mouth opening exercises were performed daily until the patient' s symptoms improved. The improvement rate was calculated as the percentage of improved cases among the total number of cases in each group. Results: The improvement rates were 27 %, 43 %, 56 %, 62 %, 65 %, and 71 % after 2, 4, 6, 8, 10, and 12 weeks, respectively. Improvement to a TMJ classification of no dysfunction was achieved in 11 % of the patients. Conclusion: This combination therapy (steroid injection) is an effective primary treatment because the improvement rate was as higher as 71 %, and 11 % of all patients had improved to a TMJ classification of no dysfunction.